Ikhwanul Muslimin, Ide-ide Persatuan Politik Kaum Muslimin, dan Pengaruhnya di Indonesia - Muhammad Nur Abduh (Tumanurung: Jurnal Sejarah dan Budaya, 2025)
This article aims to examine Hasan al-Banna’s political and social ideas through the Muslim Brotherhood movement, as well as their influence on the development of the Islamic movement in Indonesia. The research method used is a literature study with a historical-critical approach, analyzing Hasan al-Banna’s life journey, his preaching strategy, and the political dynamics involving the Muslim Brotherhood in Egypt. The research results show that Hasan al-Banna succeeded in building a movement that was able to integrate da’wah and politics, inspiring similar movements in various countries, including Indonesia. His ideas about Islam as a comprehensive solution to social and political problems influenced movements such as the Prosperous Justice Party (PKS) and the Campus Da’wah Institute (LDK). This research shows that Hasan al-Banna’s thoughts continue to live and play a role in shaping the direction of contemporary Islamic movements, both on a local and global scale.